Negotiating cohabitation in a Nigerian abattoir: One Health perspectives of human-animal-ecosystem interactions examined in the light of the SARS-CoV-2 pandemic - Hellena Debelts; Valerie Allendorf; Olayinka Asala; Ebere Roseann Agusi; Ismaila Shittu; Oluyemi Ogunmolawa; Judith Bakam; Bitrus Inuwa; Jeremiah Ijomanta; Joshua Seyi Oyetunde; Chinonyerem Chinyere; Austine Elah; et al. (One Health Outlook)
Abstract Background Urbanization and intensifying interactions between humans, animals, and the environment present complex challenges for One Health, particularly in regions like Central Nigeria. This study investigates the dynamics of human-animal-environment interfaces within a Nigerian abattoir during the ongoing SARS-CoV-2 pandemic, focusing on zoonotic transmission pathways and multispecies interactions. Methods We employed a mixed-methods approach, combining ethnographic observations, semi-structured interviews, and biological sampling of livestock, dogs, and small mammals. Virological analyses included RT-qPCR for SARS-CoV-2 RNA detection and ELISA for antibody identification. Fieldwork spanned rainy and dry seasons in 2022 to capture seasonal variations in human-animal interactions. Results The abattoir compound is centre of life of multiple species, involving humans, livestock, synanthropic mammals, and domestic animals, and as such, serves as a dynamic hub for their interactions. Seasonal changes influence interaction intensity, with higher densities during the rainy season. While SARS-CoV-2 RNA was not detected in animal samples, antibodies were identified in cattle, goats, sheep, dogs, and shrews, with higher occurrence in the rainy season. These findings suggest prior exposure of the animals to SARS-CoV-2, underscoring the influence of environmental and human behavioural factors on zoonotic transmission risks. Conclusions This One Health study demonstrates the value of integrating ethnographic insights with serological data, and highlights the abattoir compound as a critical site for zoonotic pathogen circulation. Findings emphasize the need for targeted interdisciplinary surveillance and mitigation strategies in high-density, multispecies environments to address zoonotic disease risks and enhance health resilience across species.